The impact of oxygen content on Staphylococcus epidermidis pathogenesis in ocular infection based on clinical characteristics, transcriptome and metabolome analysis - Lv, Hongling; Zhang, Wenjia; Zhao, Zhu; Wei, Yingpu; Bao, Zhengyilin; Li, Yizheng; Hu, Zhulin; Deng, Deyao; Yuan, Wenli (Frontiers in Microbiology, 2024)
This study aims to delineate the etiology and prevalence of isolated pathogens, along with the clinical characteristics of endophthalmitis patients over a 9-year period at hospital in Southwest of China. Additionally, we investigating the metabolic and cellular processes related to environmental factors may offer novel insights into endophthalmitis. For this, we analyzed data pertaining to endophthalmitis patients treated at the Affiliated Hospital of Yunnan University from 2015 to 2023. According to our clinical data, we conducted an experiment based on transcriptomics and metabolomics analysis to verify whether environmental factors affect behavior of S. epidermidis by culturating S. epidermidis under oxic and microoxic condition. In this study, 2712 fungi or bateria strains have been analyzed, gram-positive bacteria constituted 65.08%, with S. epidermidis being the most predominant species (25.55%). Ophthalmic trauma was the primary pathogenic factor for S. epidermidis ocular infections. Regarding fluoroquinolones, S. epidermidis exhibited the higher resistance rate to levofloxacin than moxifloxacin. Moreover, our investigation revealed that S. epidermidis in microoxic environment increase in energy metabolism, 字体颜色: 红色 设置格式[Administrator]: (51.4%) 删除[Administrator]: 删除[Administrator]: (15.8%) 删除[Administrator]:amino acid metabolism, and membrane transport. Our findings underscore the significance of S. epidermidis as a crucial pathogen responsible for infectious endophthalmitis. It is crucial to exercise vigilance when considering Levofloxacin as the first-line drug for empiric endophthalmitis treatment. The metabolites alteration observed during the commensal-to-pathogen conversion under microoxic condition serve as a pivotal environmental signal contributing to S. epidermidis metabolism remodeling, toward more pathogenic state.